Immunomodulatory effects and mechanisms of Qi-Xu-Tiao-Ti formula in Qi-deficiency constitution: a randomized controlled trial integrated with multi-omics and network pharmacology analysis - Cui, Renyun; Fan, Ming; Yang, Chengzhi; Chen, Cheng; Xia, Jinlu; Liu, Xi; Zhang, Guohui; Li, Fangli (Frontiers in Immunology, 2025)
BackgroundThe Qi-deficiency constitution (QDC) is a body constitution type characterized by weakened immune function and increased susceptibility to infectious diseases. Emerging evidence indicates that Chinese herbal medicine can effectively improve immunological competence in individuals with QDC. This study aims to systematically evaluate the clinical efficacy of the Qi-Xu-Tiao-Ti Formula (QXTTF) in alleviating QDC and elucidate its underlying pharmacological mechanisms through transcriptome sequencing and network pharmacology approaches.MethodsThis single-center randomized controlled trial was performed using QXTTF to treat the QDC subjects, with Balanced constitution (BC) as the healthy controls. Primary outcome measures focused on traditional Chinese medicine constitution assessment of QDC scores, with secondary evaluation parameters including immune biomarkers (IgA and IgG levels) and adverse events monitoring. To investigate the molecular mechanisms, we performed transcriptomic profiling to identify QXTTF-responsive gene targets, followed by integrated network pharmacology analysis, molecular docking simulations to characterize the compound-target interactions underlying QXTTF’s therapeutic effects, and ultimately validated at the proteomics level.ResultsThis study recruited 78 participants, comprising 63 QDC and 15 BC individuals. Comparative analysis between QDC and BC groups revealed significant differences in immunoglobulin IgA, IgG levels, and transcriptomic profiles. QXTTF intervention on QDC subjects significantly reduced the QDC scores (p < 0.05) and enhanced IgA and IgG production (p < 0.01), indicating QXTTF’s dual efficacy in constitution regulation and potential immunomodulation. Transcriptome sequencing identified eight putative therapeutic targets: ATP2A1, GOT1, SLC16A8, FTCD, ERBB2, GSS, VLDLR, and IL2. Functional enrichment analysis revealed significant overrepresentation of differentially expressed genes in immune-related pathways, notably “natural killer cell-mediated cytotoxicity”, “T cell receptor signaling pathway”, and “B cell receptor signaling pathway”. Molecular docking simulations confirmed stable binding conformations between QXTTF’s potential active components (luteolin, quercetin, naringenin) and key targets ERBB2, GOT1, and IL2. Proteomic profiling unveiled statistically significant correlations (p < 0.05) between the expression levels of core immune pathway-associated proteins and putative therapeutic targets.ConclusionsOur study demonstrates that QXTTF potentially mitigates QDC via immunomodulatory mechanisms. with therapeutic targets systematically identified through network pharmacology analysis and subsequently validated by molecular docking and proteomic profiling. These insights are crucial in delineating the pharmacological mechanisms of Chinese herbal formulas that augment the immune function of QDC, thus establishing a scientific basis for the early prevention and management of immune-related diseases.Clinical trial registrationhttp://www.chictr.org.cn/, identifier ChiCTR2200063044.